DCF (Dieng Culture Festival), Wujud Harmonisasi antara Kearifan Lokal, Agama dan Sosial Ekonomi di Masyarakat Dataran Tinggi Dieng - Gayatri Dyah Suprobowati (Universitas Sebelas Maret, 2021)
The purpose of this study is to determine the role of local wisdom values in the Dieng Cultural Festival (DCF) as a form of harmonization between local wisdom values, religion and socio-economics in the Dieng Plateau Community. The role formulation was developed based on the findings of field studies which were analyzed comprehensively by harmonizing unwritten law (custom) and religious teachings and the Dieng highlands community as well as written law (positive law). The people of the Dieng plateau are part of the Javanese tribe. However, because of the ingrained Javanese culture, the people of the Dieng plateau are adherents of the syncretistic Islam. For example, there are still Javanese traditional rituals that smell of animism and dynamism. The phenomenon that occurs in the people of the Dieng highlands is the presence of dreadlocked children. There are various groups and religions in Dieng. The result of mutual understanding and respect for each other is that religious tolerance is maintained in the area as a form of preventing social conflict. This research is a sociolegal research with empirical method by exploring primary data sources from the Dieng community. Secondary data in the form of primary, secondary and tertiary legal materials. The data collection instruments used interviews, Focus Group Discussions (FGD) and literature studies on customary law for conflict prevention. Analysis of qualitative model data with theoretical interpretation and generalization is drawn as an ideal formulation (ius constitutum). The research plan that will be carried out is to formulate the role of local wisdom values in DCF, with the stages (1) describing the values that are used as sources of local wisdom contained in DCF in the Dieng Plateau Community; (2) Analyzing whether local wisdom values in DCF can act as a means to strengthen harmonization in relation to religion and socio-economics in the Dieng Plateau Community in the perspective of Law no. 7 of 2012 concerning Handling Social Conflict. The research output is in the form of accredited national journal publications.